2013
DOI: 10.3389/fpsyg.2013.00789
|View full text |Cite
|
Sign up to set email alerts
|

Expectations in culturally unfamiliar music: influences of proximal and distal cues and timbral characteristics

Abstract: Listeners' musical perception is influenced by cues that can be stored in short-term memory (e.g., within the same musical piece) or long-term memory (e.g., based on one's own musical culture). The present study tested how these cues (referred to as, respectively, proximal and distal cues) influence the perception of music from an unfamiliar culture. Western listeners who were naïve to Gamelan music judged completeness and coherence for newly constructed melodies in the Balinese gamelan tradition. In these mel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 46 publications
1
5
0
Order By: Relevance
“…Second, the rapid learning found in this study supports that particular knowledge of a piece—even when it stems from a foreign musical culture—may be picked up during its performance (this is consistent with strong online learning found by Rohrmeier et al., ; or, Stevens, Tardieu, Dunbar‐Hall, Best, & Tillmann, ; Tillmann & McAdams, ; as well as computer models, Rohrmeier, ). In this case, the exposition of the melodic features during the ālāp section may indeed be sufficiently rich to make possible not only recognition of the features, but also elicitation of some emotional effects resulting from predictive knowledge (Huron, ; Rohrmeier & Koelsch, ), as well as appreciation of the elaboration and variation of these features in the joṛ section.…”
Section: Discussionsupporting
confidence: 88%
“…Second, the rapid learning found in this study supports that particular knowledge of a piece—even when it stems from a foreign musical culture—may be picked up during its performance (this is consistent with strong online learning found by Rohrmeier et al., ; or, Stevens, Tardieu, Dunbar‐Hall, Best, & Tillmann, ; Tillmann & McAdams, ; as well as computer models, Rohrmeier, ). In this case, the exposition of the melodic features during the ālāp section may indeed be sufficiently rich to make possible not only recognition of the features, but also elicitation of some emotional effects resulting from predictive knowledge (Huron, ; Rohrmeier & Koelsch, ), as well as appreciation of the elaboration and variation of these features in the joṛ section.…”
Section: Discussionsupporting
confidence: 88%
“…It is therefore also necessary to consider empirical studies of learned familiarity with contemporary music. For example, Western listeners may acquire knowledge of the structure of non-Western music through exposure (Stevens et al, 2013), and both musicians and nonmusicians may acquire knowledge of sequences of melodies through exposure to a new musical grammar (Rohrmeier et al, 2011). On the other hand, studies have suggested that non-tonal music may be more difficult to store in working memory than tonal music for both musicians and non-musicians (Krumhansl, 1979).…”
Section: Introductionmentioning
confidence: 99%
“…In relation to pitch, musicians and tone language listeners show an advantage in perceiving lexical tones and musical pitch, respectively, since both groups have experience in statistical learning of pitch-based elements and therefore are more likely to attend to pitch in any given input than listeners who may not have pitch experience. While it appears that non-musicians, too, use statistical learning to acquire implicit musical knowledge in their native musical system (e.g., Tillmann and McAdams, 2004 ; Bigand and Poulin-Charronnat, 2006 ; Stevens et al, 2013 ), non-musicians may not show cross-domain transfer relative to musicians presumably because non-musicians do not engage in statistical learning of musical pitch to the same extent as musicians. Evidence suggests that the active, purposeful nature of musical training in perceiving and producing musical pitch that musicians experience has consequences for acquiring musical knowledge more efficiently as opposed to listeners who acquire musical knowledge passively ( Trainor et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%